STUDENT FLOURISHING IN TERM OF SUBCULTURES IN BENGKULU CITY AND THE IMPLICATIONS OF GUIDANCE AND COUNSELING - Anna Ayu Herawati; Vira Afriyati (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2023)
Research related to flourishing has so far been centered on the western context and limited to the context of education in Indonesia. Even though Indonesia is a plural country that requires studies related to this topic to encourage a harmonious atmosphere for students in the educational environment. Flourishing students refers to the condition of individuals who are able to achieve optimal development and function fully . This study aims to describe the profile of student flourishing in terms of the Bengkulu subculture. There are six different tribes in this study consisting of Serawai, Rejang, Lembak, Javanese, Minangkabau and Batak. This research is a quantitative research with a survey type. A total of 360 students from 5 (five) major universities in Bengkulu Province filled out the survey. The instrument used is the flourishing scale ( PERMA Profile measure ), which was adapted from Julie Butler Margaret L. Kern (2016). Data analysis used descriptive analysis and the Kruskal Wallis statistical test . The results showed that the respondents had different tendencies in describing the flourishing conditions of each subculture. This research is an empirical fact that students have a level of flourishing which is still classified as moderate, and there are still many students in the low category. Each description of the flourishing of Bengkulu subculture students can be seen from the results of each indicator obtained.